EFFECT OF POLITICAL PARTIES ON THE DEVELOPMENT OF POLITICAL AND ADMINISTRATIVE PROCESSES - Reshevets I.V. (Pressing Problems of Public Administration, 2017)
In the article the essence of political parties and their role in government. The essence of the politicalprocess, and it functions in political parties. The questions of interaction of state and political parties.The in uence of political parties on the development of political and administrative processes andparticipation of political parties in the political and administrative activities of the state.